Strategic uses of vague expressions in Indonesian political talk show Mata Najwa: A pragmatic discourse analysis - Sri Handayani; Prapti Wigati Purwaningrum (Universitas Ahmad Dahlan, 2026)
The use of vague expressions in political discourse interaction is often viewed as a form of linguistic ambiguity, however, previous research has not adequately explained their strategic function in confrontational public interactions, especially in the in the context of political talk shows. This study aims to examine the pragmatic function of vague expressions as a communication strategy in the Mata Najwa talk show episode